INTERAKSI ANTAR AKTOR DALAM UPAYA MENGATASI PERMASALAHAN PASCA BENCANA ERUPSI MERAPI: Studi Kasus di Desa Glagaharjo, Kecamatan Cangkringan, Kabupaten Sleman, Yogyakarta - , ERNITA RACHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mount Merapi eruption that occurred in 2010 resulted in government policies regarding disaster-prone areas. Policies made by the government have an impact on the incidence of conflict between residents. The conflict arises due to the excluded citizens and NGOs in policy-making. On one side of the conflict also caused by social envy and the firmness of the government on policies that have been made. With determines the interactions between actors involved such as governments, NGOs, researchers and the public can know clearly the role of each actor. So that the recognition of the role and the interaction between actors is expected to occur until the problems have not been resolved now why. Not only determines the role of each actor, this study also describes the role that until now has been done by each actor since before the disaster, when disaster strikes, and after the disaster. Keywords: policy, interaction, coordination, conflict.